2018
DOI: 10.1210/js.2018-00020
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Spexin Levels Negatively Correlate With Age, BMI, Fasting Glucose, and Triglycerides in Healthy Adult Women

Abstract: ContextSpexin is a newly identified neuropeptide that is involved in satiety control, glucose, and lipids metabolism. It has also been related to human diseases, such as obesity and type 2 diabetes. However, whether spexin changes with age or not is still unclear.ObjectiveThe aim of this study is to investigate the relationship between circulating spexin levels and age and to study their interaction effects on body mass index (BMI), fasting glucose, and -lipids.Design and ParticipantsThis is a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…Gu et al [12] in a study of adults with T2DM, found negative correlations for circulating spexin with blood lipids (LDL, TG). Lin et al [11] reported that spexin levels were significantly correlated with TG. Serum spexin concentrations correlated negatively with TG in obese children in the study of Chen et al [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gu et al [12] in a study of adults with T2DM, found negative correlations for circulating spexin with blood lipids (LDL, TG). Lin et al [11] reported that spexin levels were significantly correlated with TG. Serum spexin concentrations correlated negatively with TG in obese children in the study of Chen et al [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research by Kolodziejski et al [10] showed that serum spexin levels were reduced in obese women (vs. non-obese volunteers) and were negatively correlated with BMI, HOMA-IR and insulin. Lin et al [11] reported that spexin levels were negatively correlated with BMI, fasting glucose and with age suggesting a possible role of this peptide in aging-related functions and disorders. Likewise, Gu et al [12] reported lower circulating spexin levels in adults with type 2 diabetes mellitus (T2DM) as well as negative correlations of circulating spexin with blood glucose and hemoglobin A1c (HbA1c).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro , the high level of insulin induced by glucose stimulated spexin gene expression in both goldfish hepatocytes and brain cells (Ma et al., 2017). Human study shows that the serum spexin was negatively correlated with age, BMI, fasting glucose, and TG in healthy adult women, suggesting that spexin could independently predict the risk of high BMI and high fasting glucose (Lin et al., 2018a). In human adipocytes and murine 3 T3-L1 cells, spexin exhibited a stimulatory effect on lipolysis and an inhibitory effect on lipogenesis and glucose uptake (Kolodziejski et al., 2018).…”
Section: Feeding and Energy Metabolismmentioning
confidence: 99%
“…AgRP, agouti gene-related protein; ALT, alanine transaminase; AST, aspartate aminotransferase; BAAT, bile acid CoA: amino acid N-acyltransferase; BAs, bile acids; BMI, body mass index; CA, cholic acid; CART, cocaine-amphetamine regulated transcript; CCK, cholecystokinin; CDCA, chenodeoxycholate; CRH, corticotropin-releasing hormone; CYP27A1, sterol 27-hydroxylase; CYP7A1, cholesterol 7α-hydroxylase 1; CYP8B1, sterol 12α-hydroxylase; fshβ, follicle-stimulating hormone β; GalR2, galanin receptor 2; GalR3, galanin receptor 3; GCA, glycocholate; gh, growth hormone; gnih, gonadotropin inhibitory hormone; gnrh3, gonadotropin-releasing hormone 3; gthα, gonadotropin hormone α; HbA1c, hemoglobin A1c; HNF4α, hepatocyte nuclear factor 4 alpha; HS/NAFLD, hepatic steatosis/nonalcoholic fatty liver disease; KOR, κ-opioid receptor; LCFA, long-chain fatty acid; LDL-C, low-density lipoprotein-cholesterol; LH, luteinizing hormone; L-VDCC, L-type voltage-dependent calcium channel; MCH, melanin-concentrating hormone; NPY, neuropeptides Y; PCNA, proliferating cell nuclear antigen; Pdyn, prodynorphin; POMC, proopiomelanocortin; RER, respiratory exchange ratio; T2DM, type 2 diabetes mellitus; Tβ-MCA, tauro-β-muricholate; taut, taurine transporter gene; TG, triglyceride; TUDCA, tauroursodeoxycholate; ↑, increase; ↓, decrease; green arrow, promotion; red arrow, inhibition. (Partial figure originated from Lin et al., 2018a,b).…”
Section: Conclusion/perspectivesmentioning
confidence: 99%
“…method and thus no effect is seen on the renal function. Recently, in addition to the proposed functional role of SPX in lipid metabolism, glucose homeostasis and insulin resistance, serum level of SPX was found to be decreased with age in healthy women investigated (38). This suggests that SPX could be involved in aging and its related disorders.…”
Section: Functions Of Spexinmentioning
confidence: 99%